Rancang Bangun Sistem Pendukung Keputusan Seleksi Jurusan Menggunakan Metode Weight Product Di Madrasah Aliyah Negeri 4 Madiun - Amiruddin, Nur; Rahman Prehanto, Dedy; Yuli Setyawan, Aditya (Inovate, 2022)
The majors in Madrasah Aliyah Negeri 4 Madiun are conducted to lead to students ' interests and academic talents. The current curriculum guideline of K-13, the process of studying the level of Madrasah Aliyah was conducted since the beginning of entry in class X. After the selection process enters the school, the students perform tests as a series of majors. In addition there is also a calculation process by looking at the value of the player ratings and a diploma from Junior High School (SMP) and each student's poll results. Due to the large amount of data, the process is relatively long in use because it is still done with Microsoft Excel. The calculation process is still fragmented between sheet one with another sheet , not in one process at once and takes a relatively long time.Therefore, a decision support system is needed in determining the course of assessment mechanisms. Implementation techniques used in the Decision support system is The Weight Product method. Using multiplication to link the rating of the attribute, where the rating of each tribute should be first pre-loaded with the corresponding weights.This process is the same as the normalization process. Keywords: SPK, Majors, Weight Product.